Histological study of oviduct in adult Iraqi Black Goat - Baraa Qassim Dawood; Saif A. Muhson (University of Thi-Qar Journal of agricultural research, 2023)
The present study was aimed at the light microscopic examination of the oviduct and show epithelium structure of the iraqi goat oviduct, determination of the histochemical structure of the mucus secreted by epithelial cells, and muscular layers of The oviducts of Twelve healthy adult goat constituted the material of the study. using routine histological techniques by using Hematoxylin and eosin , masson trichrom for Histochemically, it was observed by using Pas Alcian Histological observations revealed that the oviduct consists of 4 layers of mucosa, submucosa, tunica muscularis and serosa. The primary and secondary folds increase both in number and in height in infundibulum and ampulla while less in number in isthmus. Epithelium of folds was composed of simple columnar, although seems pseudostratified in some areas, and contains ciliated and secretory cells. Histomorphometric examinations of three regions demonstrated that the mean height of primary folds increase and the mean thickness of tunica muscularis in isthmus The mean thickness of mucosa-submucosa in ampulla More visibility of the ciliated cells and mucosal folds in infundibulum and ampulla the thick tunica muscularis in isthmus transports sperm cells up; and both require promoting secretory products were increased in the tip of the mucosal fold than in the base. Conclusion By using light microscopic examinations lined by pseudo-stratified columnar epithelium. Mucosal folds were maximum in number in the tubual part of infundibulum, ampulla and least in isthmus in all stages of the animal. The propria–submucosa was comprised of loose connective tissue with blood vessels, abundant amount of collagen fibres and few reticular fibers histochemical staining demonstrated by means of the PAS reaction, and it was observed that secretion increased progressively towards the isthmus.